Turboexpanders and process applications - Bloch, Heinz P., 1933-; Soares, Claire (Boston : Gulf Professional Pub., 2001)
Turboexpanders and Process Applications offers readers complete application criteria, functional parameters, and selection guidelines. This book is intended for the widest possible spectrum of engineering functions, including technical support, maintenance, operating, and managerial personnel in process plants, refineries, air liquefaction, natural gas separation, geothermal mining, and design contracting. The text distinguishes between cryogenic turboexpanders that are used to recover power from extremely cold gases, and hot gas expanders that accomplish the same objective with gases reaching temperatures in excess of 1000 degrees Fahrenheit. The authors have assembled in this book an optimum combination of process and mechanical technologies as they apply to turboexpanders. A highly practical, well-illustrated, and up-to-date overview of turboexpander construction features Appeals to a wide range of engineers.
Why Turboexpanders Are Applied; Overview Of Turboexpander Fundamentals; Application Of Cryogenic Turboexpanders: Processes; Applications Of Hot Gas Turboexpanders; Overview Of Turboexpander Construction Features; Rotor Dynamics; Construction Materials; Fabrication Issues; Installation Guides; Turboexpander Maintenance; Failure Analysis And Troubleshooting.
Includes bibliographical references and index.
Keywords: Turboexpanders; Heat recovery; Electronic books